Dampak Penggunaan Media Gambar pada Materi Tumbuhan dan Hewan di Kelas 5 SDN. 060875 Seihati - Febry Nurhayati Br Sagala; Yesica Nainggolan; Enjel Ika Barus; Syahrial Syahrial (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study observes the impact of the use of image media in learning plant and animal materials in grade 5 of elementary school. 060875 SEIHATI. This science material is often abstract, making it difficult for students to understand. The purpose of the research is to find out whether image media can increase students' understanding, interest, and activeness in learning. The method used is direct observation when the teacher uses image media (for example, printed or digital images) in learning. As a result, image media has been proven to make students more interested and motivated to learn. Abstract concepts become easier to understand because they are visualized with images. Students' memory also improves, and they are more active in discussions. Picture media helps students see plants and animals that may not exist in their surrounding environment. However, the images must be of good quality and used in conjunction with other learning methods. In conclusion, image media is very helpful in learning science of plant and animal materials in grade 5 of elementary school, so that learning becomes better and more effective. Teachers are advised to choose the right images, combine them with other learning activities, and engage students in use of image media.